The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the EACL 2009 Workshop on Language Technology and Resources for Cultural Heritage, Social Sciences, Humanities, 2009
DOI: 10.3115/1642049.1642053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the pairwise string alignment of pronunciations

Abstract: Pairwise string alignment (PSA) is an important general technique for obtaining a measure of similarity between two strings, used e.g., in dialectology, historical linguistics, transliteration, and in evaluating name distinctiveness. The current study focuses on evaluating different PSA methods at the alignment level instead of via the distances it induces. About 3.5 million pairwise alignments of Bulgarian phonetic dialect data are used to compare four algorithms with a manually corrected gold standard. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 18 publications
0
27
0
1
Order By: Relevance
“…In dialectometry (Wieling et al, 2009), the segment-segment similarity matrix is estimated using pointwise mutual information (PMI). The PMI score for two sounds x and y is defined as followed:…”
Section: Phylogenetic Approaches 321 Automatic Cognate Detectionmentioning
confidence: 99%
“…In dialectometry (Wieling et al, 2009), the segment-segment similarity matrix is estimated using pointwise mutual information (PMI). The PMI score for two sounds x and y is defined as followed:…”
Section: Phylogenetic Approaches 321 Automatic Cognate Detectionmentioning
confidence: 99%
“…Hanks, 1990). This method was introduced by Wieling et al (2009) and found to yield superior alignments as well as acoustically sensible sound correspondences (Wieling et al, to appear). 5 As multiple speakers were interviewed in every location, we used the most frequent phonetic variant as representative of all attested PVs for every normalized form.…”
Section: Obtaining Sound Correspondencesmentioning
confidence: 99%
“…While the original Levenshtein edit distance is based on these three operations without any restrictions, later algorithms adapt this method by additional edit operations or restrictions. Wieling et al (2009) compare several alignment algorithms applied to dialect pronunciation data. These algorithms include several adaptations of the Levenshtein algorithm and the Pair Hidden Markov Model.…”
Section: Levenshtein-based Algorithmsmentioning
confidence: 99%
“…Levenshtein algorithm with distances based on PMI: Wieling et al (2009) use Point-wise Mutual Information (PMI) as the basis for segment distances. They assign different costs to segments, and use the entire dataset for each alignment.…”
Section: Levenshtein-based Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation